Program G-Koin LAZISNU Lumajang dan Minat Infak Masyarakat - Ghulam, Zainil; Ghofur, Abdul; Muzayyanah, Naila (Institut Agama Islam Syarifuddin Lumajang, 2021)
The activities of collecting zakat, infaq and alms funds cannot be separated from the management of institutions that specifically deal with ZIS through the process of planning, organizing, leadership and controlling in achieving goals. This activity is also a da'wah strategy. The Nahdlotul Ulama Amil Zakat, Infak and Alms Institution (LAZISNU) Lumajang Regency is one of the ZIS institutions located in Lumajang, its flagship program is G-Koin. the. The theory used in this study for the independent variable (G-Koin program) uses an adaptation style, because there is no theory that discusses the G-Koin program, the researcher takes the dimension of the independent variable from the technical instructions of the G-Koin program, namely there are four dimensions, the education dimension , dimensions of health, economic dimensions, social dimensions of religion. For the dependent variable (interest in community donations), the researcher uses the theory proposed by Ferdinand which states that there are four dimensions of interest, namely, transactional, referential, preferential and exploratory. This study uses a quantitative approach because it measures how much people are interested in infaq with the G-Koin program, with a total population of 6,433 nahdliyin people who have cans of coins and a sample of 97 people using non-probability sampling technique. The conclusions of this study are 1. The calculation results obtained through the F test (ANOVA) are known to have a sig value of 0.000 which means that Variable X has a positive influence on variable Y. 2. The G-Koin program on community donations interest in LAZISNU, Lumajang Regency by looking at R square = 0.440 or 44.0% and the remaining 56.0% is influenced by other variables outside this study. 3. Based on the calculations that have been made, namely the education dimension, it is known that R square is 0.357 or 35.7%, the health dimension is R square is 0.425 or 42.5%, the economic dimension is R square is 0.286 or 28.6%, and the socio-religious dimension is R square. of 0.379 or 3.9%. Keywords:G-Koin Program, Community Interest, Institution Management